GÖÇMEN ÖĞRENCİLERİN EĞİTİM-ÖĞRETİM ORTAMLARINDA KARŞILAŞTIKLARI SORUNLAR: ESKİŞEHİR İLİ ÖRNEĞİ. - BÖRÜ, Neşe; BOYACI, Adnan (Electronic Turkish Studies)
The general objective of this study is to determine both the opinions of the teachers and the immigrant students in Eskisehir Odunpazari Adult Education Centre, Eskisehir Tepebasi Public Education Center and Eskisehir Anadolu Imam Hatip High School for Girls in 2015-2016 academic year about the learning of the immigrant students in Turkey. The research was prepared based on qualitative research method. The case study research design was used in the research. The participants were chosen according to "easily reachable state sample" and from Eskisehir Odunpazari Adult Education Centre, Eskisehir Tepebasi Public Education Center and Eskisehir Anadolu Imam Hatip High School for Girls in 2015-2016 academic year. The participants consist of 13 immigrant students, 10 teachers and 1 school manager. Data were collected via interview technique. Descriptive analysis was used to analyze data. The reliability of the study was found to be 0,75. 3 main themes and 19 sub-themes were found as a result of analysis of the data collected for the overall purpose of this study. The findings were developed according to the purposes. In line with the primary objective of the study, the first theme was "the overview of immigrant students on studying in Turkey". 9 sub-themes were found under the first main theme of the study. These: (a) The immigrant students' knowledge, attitudes and behaviors for learning Turkish, (b) The economic situations, problems and the perspectives of the education of the immigrant students' families, (c) The overview of the immigrant students on Turkish teachers, (d) The overview of the immigrant students on Turkish friends and Turkish people, (e) The overview of the immigrant students on course contents, study materials, projects, home works and exams in Turkey, (f) The motivations of the immigrant students to study, (g) The overview of the immigrant students on disciplinary system in Turkish school system, (h) The overview of the immigrant students on guidance service in Turkish school system, (ı) The overview of the immigrant students on social activities in Turkey. In line with the second objective of the study, the second main theme is ‘the future plans of the immigrant students'. There was no any sub-theme. In line with the third objective of the study, the third theme was ‘the overview of the teachers on immigrant students'. 10 sub-themes were found under the third main theme of the study. These: (a) The overview of the teachers on immigrants in Turkey, (b) The overview of the teachers on the education of immigrants, (c) The overview of the teachers on Turkish language courses for immigrant students and the immigrant students' Turkish information and learning efforts, (d) The overview of the teachers on the parents of immigrant students, (e) The overview of the teachers on economic situation and family problems of the immigrant parents, (f) The overview of the teachers on the immigrant students' academic achievement and motivation to study, (g) The overview of the teachers on the discipline status of the immigration students, (h) The overview of the teachers on the communication between the immigrant students with Turkish students, (ı) The attitudes and behaviors of the teachers on motivating the immigrant students, (j) The idea, attitudes and behaviors of the school management on the immigrant students.